Artefatos de desenho em geometria como parte integrante do pensamento e da atividade: um estudo sob a luz da teoria da objetivação - Silva, Luciana Gomes da (2024)
This research, predominantly qualitative and with an exploratory approach, focused on teaching a topic of geometry. The participants were students regularly enrolled in the 7th grade of Elementary School in a state school in Rio Grande do Norte, located in the north of Natal. The theoretical framework that grounded the study was the Objectification Theory (OT), a sociocultural educational theory of learning. The objective was to investigate the ways and ways in which OT can support the teaching and learning of geometry, using geometric drawing instruments as cultural artifacts. To achieve this purpose, a pilot activity was initially applied to validate the conditions necessary for the continuation of the research. Then, tasks of geometric constructions using the compass were planned and elaborated, carried out by small groups of students and the teacher, through collaboration, discussions and reflections. In OT, learning is conceived as a collective process. Data collection was carried out through video and audio recordings during the execution of the tasks, and the analysis was based on the semiotic approach and multimodality. The result of this analysis provided the composition of our educational product, which is a booklet with guidelines and suggestions for the development of a Teaching and Learning Activity (AEA) on the use of the compass in geometry classes, from the perspective of the Theory of Objectification. The booklet was validated after its submission to the qualification examining board. The present investigation allowed us to understand how the Theory of Objectification can subsidize the teaching and learning of geometry through the realization of an activity with the use of an artifact, understanding it as an integral part of it. The role of the artifact, when manipulated throughout a classroom activity, is to enable reflections on the geometric knowledge present in the artifact in its potential form. During the activity, we observed the intense use of semiotic means by the students, especially speeches accompanied by gestures to make themselves understood. Reflections on historically and culturally constituted knowledge are fundamental for the process of transformation and formation of students as ethical, critical and reflective beings.